2015
DOI: 10.18632/oncotarget.3975
|View full text |Cite
|
Sign up to set email alerts
|

Sp1-driven up-regulation of miR-19a decreases RHOB and promotes pancreatic cancer

Abstract: Cancer treatment alters microRNA (miRNA) expression, revealing potential therapeutic targets (oncotarget). Here we treated pancreatic cancer (ASPC-1) cells with either recombinant human endostatin (rh-endostatin) or gemcitabine. Then high-throughput sequencing assay was performed to screen for altered miRNAs. Both treatments decreased levels of MiR-19a. We found that miR-19a stimulated cell proliferation, migration, invasion in vitro and tumor growth in vivo. High levels of miR-19a correlated with poor prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…The results captured the imagination of the role miR‐19a‐3p plays in disease process of PC. According to Tan et al, higher levels of miR‐19a were found in PC tissues and miR‐19a was confirmed to have tumor‐promoting effect of stimulating cell proliferation, migration, invasion in vitro and tumor growth in vivo by targeting RHOB in PC . Besides PC, miR‐19a is also frequently overexpressed in tumor cells and acts as tumor‐promoting factor in other cancer types such as lung carcinoma, colorectal cancer, cervical carcinoma, and gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The results captured the imagination of the role miR‐19a‐3p plays in disease process of PC. According to Tan et al, higher levels of miR‐19a were found in PC tissues and miR‐19a was confirmed to have tumor‐promoting effect of stimulating cell proliferation, migration, invasion in vitro and tumor growth in vivo by targeting RHOB in PC . Besides PC, miR‐19a is also frequently overexpressed in tumor cells and acts as tumor‐promoting factor in other cancer types such as lung carcinoma, colorectal cancer, cervical carcinoma, and gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to provide evidence that PITX1 expression is modulated through miR-19a-3p in GC. miR-19a is frequently overexpressed, promotes cell proliferation and the epithelial to mesenchymal transition, and inhibits cell apoptosis in lung carcinoma [36,37], osteosarcoma stem cells [38], colorectal cancer [39][40][41][42], cell renal cell carcinoma [43], oral squamous cell carcinoma [44], hepatocellular carcinoma cells [45], pancreatic cancer [46], GC [47,48], cholangiocarcinoma [49], breast cancer [50], bladder cancer [51], medulloblastoma [52], and cervical carcinoma [53]. Our findings are consistent with these data because they provide evidence that miR19a is a key regulator of the multistep processes of cancer development.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…MiR‐17‐92 cluster is regarded as the first miRNA cluster with oncogenic potential,15 the cluster includes 6 single mature miRNAs, miR‐19 has been supposed to be the key oncogenic miRNA among the six members of miR‐17‐92 cluster. MiR‐19 is located on chromosome 13 in c13orf25 16 and its expression is up‐regulated in bladder cancer, breast cancer, pancreatic cancer, gastric cancer and laryngeal squamous cell carcinoma 17, 18, 19, 20, 21. MiR‐19 promotes tumourigenesis by regulating target genes and related signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-19 is located on chromosome 13 in c13orf25 16 and its expression is up-regulated in bladder cancer, breast cancer, pancreatic cancer, gastric cancer and laryngeal squamous cell carcinoma. [17][18][19][20][21] MiR-19 promotes tumourigenesis by regulating target genes and related signalling pathways. In human B-cell lymphomas, miR-19 promotes tumour cell survival by inhibiting PTEN directly and activating AKT/mTOR pathway.…”
Section: Introductionmentioning
confidence: 99%